2010
DOI: 10.1088/0004-637x/724/1/526
|View full text |Cite
|
Sign up to set email alerts
|

BRIGHT SOURCE SUBTRACTION REQUIREMENTS FOR REDSHIFTED 21 cm MEASUREMENTS

Abstract: The HI 21 cm transition line is expected to be an important probe into the cosmic dark ages and epoch of reionization. Foreground source removal is one of the principal challenges for the detection of this signal. This paper investigates the extragalactic point source contamination and how accurately bright sources ( 1 Jy) must be removed in order to detect 21 cm emission with upcoming radio telescopes such as the Murchison Widefield Array (MWA). We consider the residual contamination in 21 cm maps and power s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
372
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 336 publications
(378 citation statements)
references
References 31 publications
4
372
2
Order By: Relevance
“…The power spectrum is reduced to the two dimensions shown here by doing a variance weighted average along annuli in the k x and k y directions. This power spectrum is similar to those shown in Datta et al (2010), with a clear wedge shape and a less contaminated EoR window (above the dashed line). The lowest k mode shown is the flat-spectrum (k = 0) mode, which would contain all the foreground power if there were no mode mixing.…”
Section: Power Spectrasupporting
confidence: 75%
See 3 more Smart Citations
“…The power spectrum is reduced to the two dimensions shown here by doing a variance weighted average along annuli in the k x and k y directions. This power spectrum is similar to those shown in Datta et al (2010), with a clear wedge shape and a less contaminated EoR window (above the dashed line). The lowest k mode shown is the flat-spectrum (k = 0) mode, which would contain all the foreground power if there were no mode mixing.…”
Section: Power Spectrasupporting
confidence: 75%
“…While these single-baseline effects are very important, the mode-mixed power in the Datta et al (2010) simulations is dominated by a multi-baseline effect that we identify in this paper. Multi-baseline mode mixing occurs when measurements from non-identical baselines are combined together to increase the power spectrum sensitivity, as they are for nearly all proposed observations.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…This relationship, known colloquially as "the wedge," was derived analytically (P12b; Vedantham et al 2012;Thyagarajan et al 2013;Liu et al 2014aLiu et al , 2014b, and has been confirmed in simulations (Datta et al 2010;Hazelton et al 2013) and observationally Dillon et al 2014). As described in P12b, the wedge is the result of the delay between when a wavefront originating from foreground emission arrives at the two antennas in a baseline.…”
Section: Calibrationmentioning
confidence: 69%